2003
DOI: 10.1200/jco.2003.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Phase III Trial Comparing Whole-Pelvic Versus Prostate-Only Radiotherapy and Neoadjuvant Versus Adjuvant Combined Androgen Suppression: Radiation Therapy Oncology Group 9413

Abstract: WP RT + NCHT improves PFS compared with PO RT and NCHT or PO RT and AHT, and compared with WP RT + AHT in patients with a risk of LN involvement of 15%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
270
1
6

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 600 publications
(282 citation statements)
references
References 30 publications
5
270
1
6
Order By: Relevance
“…[17][18][19][20] In brief, all patients received treatment with external beam radiation using megavoltage linear accelerators (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). In all three institutions, the prostate gland was boosted using two interstitial brachytherapy procedures.…”
Section: Radiation Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19][20] In brief, all patients received treatment with external beam radiation using megavoltage linear accelerators (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). In all three institutions, the prostate gland was boosted using two interstitial brachytherapy procedures.…”
Section: Radiation Techniquementioning
confidence: 99%
“…[1][2][3][4][5][6][7] As several randomized trials have shown a benefit in the treatment of prostate cancer with high-dose RT, the need for AD with the use of a high-dose technique needs to be evaluated. [8][9][10] AD when combined with low-dose radiation has been shown to be an effective adjuvant treatment and to improve overall survival for prostate cancer patients with high-risk features.…”
Section: Introductionmentioning
confidence: 99%
“…1, 2). It is noteworthy that randomized studies comparing long-term and short-term hormone use (e.g., RTOG 92-02 9 ) and those comparing different sequences of radiotherapy and hormone use (e.g., RTOG 94-13 50 ) were not included in the current study, because our model only allowed the use of studies that compared radiotherapy alone with radiotherapy plus hormone therapy. Although the model could be expanded to include individual arms of these other studies, errors and biases would be introduced by doing so.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the 2 main randomised trials evaluating whole pelvis versus prostate only EBRT are conflicting. RTOG 9413 compared whole pelvis versus prostate only EBRT and neo-adjuvant versus adjuvant combined ADT 49 . Patients with a risk of LNI >15% were included (n=1.323).…”
Section: Whole Pelvis Irradiation For Lymph Node Metastasized Pcmentioning
confidence: 99%